DEVONIAN DEEP-CRUSTAL METAMORPHISM AND EXHUMATION IN THE VARISCAN OROGEN: EVIDENCE FROM SHRIMP ZIRCON AGES FROM THE HT-HP GRANULITES AND MIGMATITES OF THE GÓRY SOWIE (POLISH SUDETES) - Kryza R.; Fanning C.M. (My University, 2007)
The high-temperature and high-pressure granulites in the internal zone of the Variscan belt are witnesses of deep crustal processes and subsequent exhumation of deeper lithospheric fragments. The Góry Sowie Block granulites in SW Poland and the surrounding gneisses and migmatites contain different inherited zircon age spectra, testifying different sources of their protoliths: mainly Cadomian (ca. 580 Ma) igneous rocks, and early Ordovician (ca. 500 Ma) granitoids (or their reworked products), respectively. The metamorphic spheric and oval zircons in the granulites give two statistically distinct ages of c. 395 and 380 Ma, in excess of experimental uncertainty. These ages may correspond to the high-temperature (HT) and high-pressure (HP) granulite facies metamorphism and subsequent amphibolite facies retrogression. However, essentially isochemical reconstitution of zircons and inheritance of radiogenic Pb cannot yet be excluded. The retrogression in the granulites coincided with the amphibolite facies metamorphism in the surrounding gneisses evidenced by a range of various isotopic ages between 384 and 370 Ma. The new SHRIMP zircon data provide new evidence of the presence of "old" (c. 400-395 Ma) HT-HP granulites in the central European part of the Variscides. The granulites were subsequently exhumed to mid-crustal levels, and tectonically interleaved with gneisses. Continuing uplift and decompression caused migmatization in the surrounding gneisses and partial re-equilibration of the granulites, at around 380 Ma. This high-temperature and medium-pressure (HT-MP) event was followed by rapid uplift and exhumation at c. 360 Ma due to Eo-Variscan orogenic movements. © 2007 Lavoisier SAS. All rights reserved.
Keywords: EXHUMATION OF HIGH-P AND HIGH-T ROCKS; GRANULITES; VARISCIDES; ZIRCON DATING; Devonian; Ordovician; Paleozoic::Devonian; Палеозой::Девонская; Paleozoic::Ordovician; Палеозой::Ордовикская